Tendência de formação de fase amorfa em ligas a base de magnésio para biomaterial temporário - Danez, Gabriela Pancev (Universidade Federal de São Carlos, 2011)
Mg alloys have attracted attention as potential implant material because of their good mechanical properties, biocompatibility and biodegradation properties. However corrosion of these alloys causes intense release of hydrogen gas which is not desirable for biomedical applications. Zberg et. al. reported a significant reduction in hydrogen evolution in Mg-Zn-Ca glassy alloys due the increase of Zn without the formation of undesirable intermetallic phases. These glassy alloys showed great potential for deployment in a new generation of biodegradable implants. In this context the evaluation of the glass forming ability (GFA) of Mg-Zn-Ca alloys, in the Mg-rich composition corner is relevant. In the present work we studied Mg-rich compositions in the Mg-Zn-Ca system based on the topological instability criterion (min) combined with the average electronegativity difference (e) among the elements in the alloy. Bulk samples were produced by rapid cooling in a copper mold and ribbons were produced by melt-spinning technique. The microstructure, amorphous nature, thermal properties and chemical composition of samples were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC) and electron dispersive spectroscopy (EDS). Best results were observed in alloys with Ca content limited to 6 at%. Furthermore, the samples ewre subjected to oxidation and high change in composition.
Evaluation of the glass forming ability in mg-zn-ca alloys for biomedical application
Keywords: Engenharia de materiais; Materiais amorfos; Solidificação rápida; Ligas de magnésio; Biomateriais; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA